Learning and transfer of object-reward associations and the role of the perirhinal cortex. - Buckley, M; Gaffan, D (1998)
Perirhinal cortex ablation has previously been shown only to impair new postoperative object discrimination learning with large stimulus set sizes (> or = 40 problems). In this study, 3 cynomolgus monkeys (Macaca fascicularis) with bilateral perirhinal cortex ablations were impaired relative to 3 normal controls on concurrent discrimination learning tasks with only 10 problems with the objects presented in different orientations in each trial to increase the demands placed on object identification. This supports the hypothesis that perirhinal cortex damage impairs the ability to identify multiple individual objects. Fewer errors were made to digitized images of objects than toward real objects. Both groups subsequently transferred specific object-reward associations from real objects to digitized images of the respective objects and vice versa, providing evidence that cynomolgus monkeys can recognize photographic representations of objects with experience.